Regulatory Frameworks In Islamic Fintech: Comparative Insights From Indonesia and Malaysia - Fidhayanti, Dwi; Mohd Noh, Mohd Shahid; Hanafi, Hanira; Satria, Muhammad Hatta (Universitas Negeri Gorontalo, 2025)
Despite the rapid expansion of Islamic fintech in Indonesia and Malaysia, research comparing the legal and regulatory frameworks in both jurisdictions remains limited. This study addresses that gap by examining the differences and challenges within each country’s legal infrastructure that impact the development and governance of Sharia-compliant financial technology. The objective of this research is to analyze and compare the regulatory systems in Indonesia and Malaysia to identify structural strengths, weaknesses, and their implications for legal certainty and financial innovation. Employing a normative juridical method with a comparative legal approach, the study analyzes statutory instruments, regulatory frameworks, and institutional roles in both countries. The findings reveal that Malaysia benefits from a more cohesive and structured legal framework under the Islamic Financial Services Act 2013, supervised by Bank Negara Malaysia and the Securities Commission, ensuring enforceable Sharia compliance and robust innovation support. In contrast, Indonesia's regulatory environment suffers from fragmented oversight between OJK and DSN-MUI, resulting in legal uncertainty and limited enforcement of Sharia principles. This research contributes to the field of Islamic financial law by offering policy recommendations to harmonize regulatory frameworks, enhance legal clarity, and promote the sustainable growth of Islamic fintech ecosystems in Southeast Asia.